STUDI NERACA AIR WADUK LAPANGAN (LONG STORAGE) DI DESA SEMANGGA JAYA KABUPATEN MERAUKE - Yosehi Mekiuw (AGRICOLA, 2013)
The study aims to determine the capacity of field accumulating basin (long storage) in supplying plants with water in the form of water balance and to determine the appropriate cropping pattern based on water availability in this reservoir. The total water available in reservoir, once evaporation and seepage rates were subtracted to it, is ± 60,056.29 m3, thus water balance is in surplus position and thereby the available water is ready to meet the crop water needs in accord with the proposed cropping pattern.